The labour supply of women in STEM - Eva Schlenker (IZA Journal of European Labor Studies, 2015)
The purpose of this paper is to assess the determinants of female labour supply in science, technology, engineering and mathematics (STEM). To account for selection problems, a special type of grouping estimator and a control function approach are implemented. Using data from EU-SILC, the author finds that women, especially mothers, in STEM work more hours, but have a higher probability of being out of the labour force. The estimation results show furthermore that women in STEM work less hours in countries with higher levels of family allowances. However, this effect is small in size compared to the overall effects of larger levels of expenditures on family allowance and child benefits.
Keywords: J22; J24; 330; Female labour supply; STEM; EU-SILC; Grouping estimator